The choreography of laman silat dance: a study of malay cultural expression at kumpulan seni seri Melayu, Riau - Nurmalinda , Nurmalinda; Efendi, Rusman; Evadila, Evadila (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
This research aims to analyze how the choreography of the Laman Silat Dance, created by Sunardi, embodies the expression of Malay-Riau culture through a combination of Malay-Riau silat movements with 'contrast' choreographic techniques. Using a qualitative approach with ethnographic methods, data was collected through participatory observation, in-depth interviews, and documentation analysis. The analysis focuses on the elements of choreography, including movement, music, costume, makeup, floor design, and lighting, as creative expression. The research findings reveal that the Laman Silat Dance expresses Malay-Riau culture through silat movements, clothing, and Malay-Riau music. The ‘contrasting’ yet dynamic choreographic composition depicts Malay-Riau culture's ‘contrasting’ yet dynamic richness. The Malay-Riau musical instruments used, poetic narration, and energetic movements with accents on the shoulders, head, and hands enrich this dance's aesthetic and narrative dimensions. Thus making it a representation of the cultural expression of Malay-Riau silat. This research contributes to the academic discourse in performing arts by highlighting the role of choreography as an artistic expression of Malay-Riau culture. The strength of this study lies in its comprehensive analysis of artistic elements as cultural expression, which offers a foundation for understanding the balance between contrast in choreography and contemporary movement in Malay-Riau culture. In addition, this research opens up opportunities for future studies to explore the influence of the Laman Silat Dance on the younger generation, especially in terms of how this dance can instill pride and cultural awareness in the midst of globalization.